WAWASAN AL-QUR’AN TENTANG KHAMR MENURUT AL-QURTHUBI DALAM TAFSIR AL-JAMI’ LI AHKAM AL-QUR’AN - Thias Arisiana; Eka Prasetiawati (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2019)
This paper explores further the concept of khamr which is intact in the Qur'an. Because khamr is increasingly playing an important role in human life. Victims of abuse of khamr in Indonesia lately also tend to increase and include not only limited to groups of the well-off, but also has penetrated among the poor in both cities and rural areas, and not only involving non-students but also involves students, especially high school students and students. With these conditions, it can be predicted that there will be a lost generation, namely the young generation lost due to drug abuse. The purpose of this study is to find out the interpretation of the verses in the interpretation of the Qurthubi so that they can become a reference for Muslims in the millennial era today. In studying this the researcher uses a type of qualitative research with a descriptive-analytic approach. The results of this study are based on the view of al-Qurthubi that the prohibition of khamr and its mention as rijsun is something unclean, so we are told to stay away not only not to drink, but also not to be sold and used as medicine